Terbentuknya Negara dalam Konsep Pemikian Ibnu Khaldun - Rolis, Mohammad Ilyas; Harnadi, Dodik (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2021)
The attention of researchers to explore the brilliant thoughts of Ibn Khaldun is so great. Khaldun is a multidisciplinary scientist. He has many statuses. However, several studies of Khaldun's thought generally focus on two main disciplines, namely sociology and politics. His prolegomena, entitled muqaddimah, record very clearly the impressions of Khaldun's thoughts in the fields of sociology and politics. Generally, the study of Khaldun's thought only takes one corner of the scientific discipline, it is sociology or politics. In fact, Khaldun's various political ideas are actually a combination of sociology and politics at the same time. The study in this paper takes a different point of view by presenting the dual ideas of Khaldun's sociology and politics. This literature study found that Ibn Khaldun was one of the leading thinker of the political sociology. His idea of ​​political sociology is reflected in Khaldun's conception of Ashabiyah and nomadic society.